2018
DOI: 10.13057/biodiv/d190633
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Growth and mortality rate of Black Pomfret Parastromateus niger (Bloch, 1795) and Silver Pomfret Pampus argenteus (Euphrasen, 1788) in Paloh Waters, West Kalimantan, Indonesia

Abstract: Damora A, Ariyogagautama D, Wahju RI, Susanto H, Wang J. 2018. Short Communication: Growth and mortality rate of Black Pomfret Parastromateus niger (Bloch, 1795) and Silver Pomfret Pampus argenteus (Euphrasen, 1788) in Paloh Waters, West Kalimantan, Indonesia. Biodiversitas 19: 2247-2251. Three species of pomfret fish were caught in Paloh waters including Parastromateus niger, Pampus argenteus, and Pampus chinensis. P. niger and P. argenteus which were more dominant than P. Chinensis. Pomfret fishing in the Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
1
Order By: Relevance
“…Another study found the value of TL as 30.9 cm from the Bay of Bengal (Cox's Bazar) which was lower than our finding (Akhter et al 2020). This maximum length (38 cm) was also smaller than the fish of 56.2 cm caught from the Persian Gulf (Sahraei et al 2018) and 45 cm from the Indonesian coast (Damora et al 2018). The information on maximum length can be used to estimate the population parameters of fish species (Hossain 2010).…”
Section: Discussioncontrasting
confidence: 60%
“…Another study found the value of TL as 30.9 cm from the Bay of Bengal (Cox's Bazar) which was lower than our finding (Akhter et al 2020). This maximum length (38 cm) was also smaller than the fish of 56.2 cm caught from the Persian Gulf (Sahraei et al 2018) and 45 cm from the Indonesian coast (Damora et al 2018). The information on maximum length can be used to estimate the population parameters of fish species (Hossain 2010).…”
Section: Discussioncontrasting
confidence: 60%
“…The number of net panels set each night varied slightly for each gillnet with the total net length ranging from 1.17 km to 1.38 km. Following the standard practice of this fishery, nets were deployed during late afternoon, soaked overnight, and retrieved by hand during early morning (Damora et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…vessel size, location, time of setting and hauling, net length), and catch information). The primary target species in this fishery included the pomfret species Pampus chinensis, Pampus argenteus, and Parastromateus niger (Damora et al, 2018). The fishery also captured several commercially valuable non-target species, which included Lutjanus griseus, Caranx sexfasciatus, Arius thalassinus, Chinocentrus dorab, Myliobatis tobijei, Himantura gerrardi Gymnura poecilura, Eletheronema tetradactylum, Chorinemus tala, and Scomberomorus commersonii, that were retained and sold (Damora et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation